PENGARUH PENDAPATAN DAN PENDIDIKAN ORANG TUA TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII SMP NEGERI 3 PANJI SITUBONDO SEMESTER GENAP - Rahmat Shofan Razaqi Razaqi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
To improve the quality of education, renewal in learning is needed, so that the teaching and learning process can run effectively with the hope of improving the quality of education, especially in improving student learning outcomes. The family is the first social institution known to the child and in this family attitudes can be instilled that can influence the subsequent development of the child. Families are responsible for providing funds for children's educational needs. The economic condition of the parents of students also supports students in the provision of learning facilities and infrastructure to obtain maximum learning outcomes. After analyzing the data, the value of the correlation coefficient between learning outcomes (Y) and parents' income (X1) was obtained regardless of parental education (X2) of 0.260. While the value of the correlation coefficient level between learning outcomes (Y) and parental education (X2) by ignoring parents' income (X1) is 0.462, as well as the value of the correlation coefficient level between the two independent variables simultaneously with the criterion Ry (1,2,3). ¬ of 0.564. In testing the minor hypothesis 1, there is a low effect of parental income on student learning outcomes, and minor hypothesis testing 2 results in a moderate effect of parental education on student learning outcomes. Furthermore, proving the major work hypothesis using the F test, the major work hypothesis will be proven if the F-count is greater than the F-table with a significant level of 5%. The F-count is 22.614 while the F-table is 3.09 at N = 100, which means that the F-count is greater than the F-table, so it can be said that there is a significant effect of parents' income and education on social studies learning outcomes of VIII grade junior high school students Negeri 3 Panji even semester.